Gastric Intestinal Metaplasia: Demographic and Epidemiological Characterization in Puerto Rican Hispanics (2012-2014) - Jorge J. Cruz-Cruz; María González-Pons; Adrián Cora-Morges; Marievelisse Soto-Salgado; Giancarlo Colón; Kimberly Alicea; Kathia Rosado; Douglas R. Morgan; Marcia Cruz-Correa (Gastroenterology Research and Practice)
Background and Aims. Gastric cancer is the 5th leading cause of cancer mortality worldwide and the leading infection-associated cancer. Helicobacter pylori is the most common chronic bacterial infection in humans and the major predisposing factor for the development of gastric intestinal metaplasia (GIM), the principal preneoplastic lesion in the gastric carcinogenesis pathway. GIM surveillance is now recommended for individuals among high-risk subgroups by three major gastroenterology societies in Europe, England, and U.S. Our objective was to provide the initial epidemiologic data for GIM among Hispanics in Puerto Rico. Methods. Using a cross-sectional study design, we analyzed an extensive pathology database (n=43,993) that captured approximately 50% of all endoscopy biopsies taken during 2012-2014 at academic, public, and private sectors in Puerto Rico. Prevalence estimates of GIM, GIM subgroups, and H. pylori status were estimated using logistic regression models. Results. A total of 4,707 GIM cases were identified during the study period for a prevalence rate of 10.7%. H. pylori was detected in 26.9% (95% CI: 25.7-28.2) of the GIM cases. The majority of the pathology reports lacked information regarding the high-risk subtypes (99.6%) and extension (71.2%). Conclusions. The prevalence of GIM among Hispanics living in Puerto Rico may be higher than in U.S. mainland non-Hispanic populations. The prevalence of H. pylori detected in our study population was comparable to the rates reported in the mainland U.S. Standardization of the endoscopy biopsy protocol and pathology reporting is needed to characterize and risk stratify GIM surveillance programs in Puerto Rico.